2012
DOI: 10.1038/nm.2896
|View full text |Cite
|
Sign up to set email alerts
|

Early infection with respiratory syncytial virus impairs regulatory T cell function and increases susceptibility to allergic asthma

Abstract: Immune tolerance is instituted early in life, during which time regulatory T (Treg) cells have an important role. Recurrent infections with respiratory syncytial virus (RSV) in early life increase the risk for asthma in adult life. Repeated infection of infant mice tolerized to ovalbumin (OVA) through their mother’s milk with RSV induced allergic airway disease in response to OVA sensitization and challenge, including airway inflammation, hyper-reactivity and higher OVA-specific IgE, as compared to uninfected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
178
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(191 citation statements)
references
References 52 publications
7
178
0
1
Order By: Relevance
“…We also determined pronounced expression of FoxP3, the cognate transcription factor for Treg cells, in lung CD4 cells of both neonates and weanling mice exposed to maternal LPS. Interestingly, increased numbers of lung Treg cells with impaired suppressor function have been reported in weanling mice with exacerbated inflammation in recurrent RSV (21). Although beyond the scope of the present studies, the effect of maternal inflammation on postnatal Treg function would be important to determine in the context of subsequent infection and is a current focus of investigation.…”
Section: Discussionmentioning
confidence: 83%
“…We also determined pronounced expression of FoxP3, the cognate transcription factor for Treg cells, in lung CD4 cells of both neonates and weanling mice exposed to maternal LPS. Interestingly, increased numbers of lung Treg cells with impaired suppressor function have been reported in weanling mice with exacerbated inflammation in recurrent RSV (21). Although beyond the scope of the present studies, the effect of maternal inflammation on postnatal Treg function would be important to determine in the context of subsequent infection and is a current focus of investigation.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, RSV is able to induce a Th2-like effector profile of the Treg cells by inducing GATA-3. This results in the loss of the Treg cell's normal suppressive function and causes allergic airway disease (85). The exact mechanisms by which RSV exerts its effect on T-cell differentiation is yet to be clarified.…”
Section: Th17 Subsetmentioning
confidence: 99%
“…+ CD25 + Tregs, as a distinct T cell subset, had an important role in pulmonary inflammatory disease including ALI (53)(54)(55). For example, one group reported that intrapulmonary delivery of human umbilical cord mesenchymal stem cells could attenuate the development of ALI through Treg (56).…”
Section: Cd4mentioning
confidence: 99%